The future of critical theory: on the courage and limitations of Bernard Harcourt's Critique & Praxis. Issue 1 (3rd April 2021) - Davis, Benjamin P.
ABSTRACT: This review essay examines prominent definitions of Critical Theory today. Many of these definitions frame Critical Theory as a broad project that distinguishes itself from other theories by working across disciplines in order to contribute to emancipatory movements. Defined thus, Critical Theory serves as an umbrella term under which would sit, for instance, feminist, decolonial and intersectional theories. But when elaborating on their definitions of Critical Theory in public statements, several prominent institutional sites and recent books chart a lineage from Immanuel Kant to the Frankfurt School and beyond, highlighting recent debates with French poststructuralism. When the story of Critical Theory is told in this way, Critical Theory runs into the problems Bernard Harcourt effectively outlines in Critique & Praxis, such as retreating from political practice into epistemological questions, withdrawing from activism into academic enclaves and being co-opted by liberal politics. My argument is that certain figures advancing Black radical thought and cultural critiques—I focus on Joy James and Stuart Hall—give Critical Theory the theoretical and practical resources to side-step the problems of retreating into epistemology, the academy or liberalism. Re-oriented in this way, Critical Theory could more effectively diagnose and respond to the struggles of our time.